Synthesis of Gemini‐QA N‐Chloramine Biocides for Antibacterial Applications. Issue 45 (3rd December 2019) - Li, Lingdong; Wang, Hande; Jia, Dongxue; Wang, Pengfei
Abstract: Gemini‐quaternary ammonium (QA) N ‐chloramines were synthesized by covalently bonding two N ‐chloramine units via a Gemini‐QA core with varied alkyl linkers. Preliminary antibacterial tests showed that Gemini‐QA N ‐chloramine exerted superior biocidal efficacy in contrast to previous developed QA N ‐chloramine counterpart probably by means of "team effort" contact killings. Futhermore, the analog with linker of ‐(CH2 )10 ‐ exhibited the highest antibacterial efficacy probably caused by its favorable membrane penetration. This work may provide vital references to develop multi‐cationic N ‐chloramines with even higher biocidal activity, which may be indispensable for combateing with bacteria resiatance. Abstract : For the first time Genimi QA N ‐chloramines were synthesized with drastically higher antibacterial efficacy (n=1) in comparison with QA N ‐chloramine 1, and the highest biocidal efficacy was achieved for the N ‐chloramine analog with the longest linker of ‐(CH2 )10 ‐ (n=8).